Subnetwork and transmission path for voltage security reinforcement / Azhar Shahidan - Shahidan, Azhar (2016)
This thesis presents the formation of subnetwork and transmission path for voltage security reinforcement. The aim is to identify the weakest bus from the voltage stability point of view, the most loaded transmission path for that bus, again from voltage security point of view.